By-products of Scyliorhinus canicula, Prionace glauca and Raja clavata : a valuable source of predominantly 6S sulfated chondroitin sulfate - Novoa-Carballal, R. (2017)
Chondroitin sulfate (CS) was isolated from Scyliorhinus canicula (fin, head and skeleton), Prionace glauca (head), and Raja clavata (skeleton) by-products from fish processing industry using environmentally friendly processes. The molecular weight was determined by gel permeation chromatography and the sugar composition and sulfation position by NMR and SAX-HPLC after enzymatic digestion. The CSs showed a prevalent 6S GalNAc sulfation for the 3 species (4S/6S ratio lower than 1). A higher 6S sulfation was observed for P. glauca head and R. clavata skeleton (4S/6S ratio below 0.20) than for S. canicula (4S/6S ratio ca. 0.6). The existence of CS samples with such low 4S/6S ratio has only been observed before in a rare species of shark (Mitsukutina owatoni, globin shark). The good extraction yields achieved make S. canicula, P. glauca and R. clavata fish industry by-products a useful source of 6-sulfated chondroitin sulfate.